Lost time? Renato Russo's poetics in the context of the cultural industry - Klein, Juliana Beatriz (2005)
This work, by analyzing the song “Tempo perdido” (Dois, 1986), by Renato Russo, intends to emphasize a striking feature of the composer, namely, the fact that he does not necessarily have to rely on explicit elements of denunciation to being able to exercise social criticism, but expressing it through the perplexity of the lyrical subjects. We believe that, in addition to the fact that the medium does not determine the work, with the characteristics of the Cultural Industry not being reflected in the objects produced by the author, the demand for improvements also does not need to go through “pamphleting”.